PENGARUH PENAMBAHAN ABU TONGKOL JAGUNG TERHADAP SIFAT FISIS DAN MEKANIS PADA MORTAR - Pulung Karo Karo; Rio Orlando Pratama; Roniyus Marjunus (Journal of Energy, Material, and Instrumentation Technology, 2023)
The research was carried out about the effect of adding corn cob ash on mortar's physical and mechanical properties. Mortar was molded with three compositions, i.e., portland cement, corn cob ash, and corn husk fiber. Corn cob ash was burned at a temperature of 700  for 2 hours. Corn husk fiber was mechanically sliced up to 0.8 mm in size. Then, mortar molding and maintenance were processed for 28 days. The mortars that had reached the age of 28 days were tested according to the Indonesian National Standard (SNI), including physical properties (density) and mechanical properties (compressive strength, flexural strength, splitting tensile strength). Characterization of microstructure, morphology, and composition of all elements on the mortar's surface was processed using Scanning Electron Microscopy-Energy Dispersive X-ray Spectroscopy (SEM-EDS). The research results show the influence of adding corn cob ash on mortar's physical and mechanical properties. The mortar with the most optimum physical and mechanical properties has a composition of 82:6:12. The characterization results using SEM-EDS show that the surface of this composition sample is better than other samples. The most dominant elements in the mortar are elements of Ca and Si, which function as mortar binders and hardeners.